Pembuatan Indeks Artikel Surat Kabar Beranotasi Bidang Hukum Periode Juli - Desember 2014 di Perpustakaan Kantor Wilayah Kementerian Hukum dan Hak Asasi Manusia Sumatera Barat - Chandra, Deri; Marlini, Marlini (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2015)
This article aims to describe the process of making an annotated index of newspaper articles in the legal field Libraries Regional Office of the Kementerian Hukum dan Hak Asasi Manusia Sumatera Barat period from July to December 2014. The method used in this research is descriptive method. Making the annotated index of newspaper articles in the field of law at the Library of the Regional Office of the Kementerian Hukum dan Hak Asasi Manusia Sumatera Barat period from July to December 2014 carried out by direct observation and data collection from the original source, namely the newspaper clippings that existed at the Library of the Regional Office of the Kementerian Hukum dan Hak Asasi Manusia Sumatera Barat. Stage in the legal field annotated indexes performed as follows: (1) the recording of the article that was published in newspaper clippings Library Regional Office of the Kementerian Hukum dan Hak Asasi Manusia Sumatera Barat; (2) make a description of the article; (3) make annotations; (4) specify keywords; (5) makes the index a newspaper article; (6) make up an index of articles; (7) typing the index. Keywords: Index, articles, newspapers, annotated, law